O litoral habitado: uso residencial na costa oeste cearense - Vieira, Kaio Duarte (2024)
Tourism and maritime travel are vectors of urbanization on the coast of Ceará. These activities are linked to the emergence and spread of occasional residences, popularly known as summer houses. However, permanent residential use predates such practices, and this typology is mainly associated with fishing communities. Thus, residential use on the coast has two typologies. The west coast of Ceará has undergone a series of socio-spatial transformations resulting from the economic policy of tourism, which has accentuated the process of metropolization and reinforced the growth of occasional homes. These facts explain the choice of Caucaia, Trairi and Cruz in this study. Among the qualitative and quantitative changes is the socio-spatial fragmentation of the urban fabric guided by the duality of leisure and occasional housing on the coast. From these conceptual perspectives, the operationalization of the analytical tools was based on an accurate state of the art, census operations carried out by the IBGE (2000, 2010 and 2022), hemeroteca, GIS software, satellite images, as well as the secondary data platform provided by IPECE, CADÚnico and SIDRA-IBGE. As a result, it was possible to establish two logics of urban-coastal occupation in Ceará. The first refers to occasional use, located in areas parallel to the beach, which is currently more expressive with tourist real estate developments. In Caucaia, specifically in Icaraí, the form of occupation parallel to the beach is for occasional and permanent high-income use. This is not the case for the entire coastline of the municipality, nor for Trairi and Cruz, where the residential use profile is for occasional and permanent low- income use, parallel to the beach, a similar case for sectors of the Caucaia coastline, such as Cumbuco, Iparana and Pacheco. The second perspective corresponds to the form of occupation peripheral to the beach, in which occasional use is absent or less expressive, the figure of the inhabitant is for the totality of the occupation, as well as the greater concentration of families with an income of less than or equal to 1 minimum wage. Both logics of occupation on the coast are reinforced by the economic valuation of the beach and coastal urban land, so they were observed and analyzed in a complementary and juxtaposed way.